Meningkatkan Hasil Belajar Siswa Menggunakan Model Teams Games Tournament Berbantuan Peta Pintar - Roudlotun Nofiati Bimashiatillah; Deka Setiawan; Much Arsyad Fardani (STKIP Andi Matappa Pangkep, 2020)
This study aims to improve student learning outcomes with the application of the Teams Games Tournament model assisted by Smart Map media on the theme Beautiful Diversity in My Country Grade IV students in SDN Penggung 01. Based on the results of the PTS private pre-cycle of students, data obtained that the PPKn content of students who completed 6 of 16 students with a percentage of 37.5% and on the Indonesian Language content students who completed 7 of 16 students with a percentage of 43.75% (according to KKM ≥ 75). The research method used was classroom action research (CAR) which consisted of two cycles. The subjects of the research were grade IV students of SDN Penggung 01, this study used four components namely planning, implementing, observing, and reflecting. Data collection is done by observation, interviews, tests, and documentation. The results of the study in the first cycle showed that the PPKn content with the percentage of classical completeness 68.75% and the Indonesian content percentage of classical completeness 68.75%, increased in the second cycle with the percentage of classical completeness 93.75% at the PPKn content and 87.5 % of Indonesian content. This proves that the Teams Games Tournament learning model can improve student learning outcomes.